Axiology of lego-lego dance in sports perspective - Nyoman Wali, Carles; Komarudin; Pranata, Doni (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
The axiology of lego-lego dance in a sports perspective is a study that explores the values ​​contained in lego-lego dance, especially sports axiology. This study aims to determine/find the axiology of sports contained in the lego-lego dance which is studied through the perspective of sports in the lego-lego circle. This research method is a quantitative descriptive method using observation, interviews and questionnaires. The subjects in this study involved 50 people from the West Kuligang Pantar tribe, Alor Regency, East Nusa Tenggara. The data collection of this research used descriptive quantitative by using a questionnaire. The data analysis of this research is using the MIX method, a combination of quantitative and qualitative, the data to be analyzed can then be drawn conclusions according to the focus of the problem being studied. The results of this study indicate that sports axiology in lego-lego dance really exists with respondents' answers presented as Strongly Agree (SS) 1,92%, Agree (S) 2,80%, Neutral (N) 1%, Disagree (TS) 0,08% . The limitation of this research is that the single version of the lego-lego dance is not plural because the lego-lego dance in each tribe has different movements, sources, subjects, places of research and times. Researchers hope that there are researchers who can examine more than one version of the lego-lego dance.